A Review of Diabetes Mellitus–Specific Family Assessment Instruments. (April 2013) - Song, MinKyoung; Deatrick, Janet A.; Feetham, Suzanne L.; Levin, Amy
Family dynamics and attributes are increasingly recognized as affecting management of diabetes mellitus (DM); however, little research has been done on the validity and usefulness of family assessment instruments (FAIs). This article reviewed the literature that employs DM-specific FAIs and evaluates whether the instruments comprehensively captured family attributes/processes and were robust enough to be useful in understanding the relationship between family attributes/issues and DM-related health care. Studies using eight instruments were identified through a search of literature published from 1982 to 2010 and were analyzed with criteria derived from the measurement and family literatures. The findings of this study revealed that DM-specific FAIs yield useful data about family-related phenomenon; however, some domains of DM-specific care, such as family dynamics/functioning, were not overtly measured. Suggestions for improving DM-specific FAIs are provided and a rationale for why DM-specific and non-DM-specific FAIs is needed to fully measure family issues related to family dynamics/attributes on DM patient care.